2010
DOI: 10.1159/000314308
|View full text |Cite
|
Sign up to set email alerts
|

Lithium’s Emerging Role in the Treatment of Refractory Major Depressive Episodes: Augmentation of Antidepressants

Abstract: Background: The late onset of therapeutic response and a relatively large proportion of nonresponders to antidepressants remain major concerns in clinical practice. Therefore, there is a critical need for effective medication strategies that augment treatment with antidepressants. Methods: To review the available evidence on the use of lithium as an augmentation strategy to treat depressive episodes. Results: More than 30 open-label studies and 10 placebo-controlled double-blind trials have demonstrated substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 84 publications
3
58
0
5
Order By: Relevance
“…The plasma levels of lithium after 1 week of 0.2% Li 2 CO 3 treatments are within the recommended therapeutic range (0.5-1.2 mEq/l) (Suppes et al, 2008: Bauer et al, 2010.…”
Section: Drugmentioning
confidence: 56%
See 1 more Smart Citation
“…The plasma levels of lithium after 1 week of 0.2% Li 2 CO 3 treatments are within the recommended therapeutic range (0.5-1.2 mEq/l) (Suppes et al, 2008: Bauer et al, 2010.…”
Section: Drugmentioning
confidence: 56%
“…Recently, many augmentation strategies have been developed to increase the effectiveness of antidepressant drugs. One such approach used in the treatment of psychiatric disorders is the addition of lithium to antidepressant drugs (Bauer et al, 2010;Chenu and Bourin, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[34] However, owing to a lack of RCTs that directly compared lithium to other augmentation agents RR = response rate; OR = odds ratio; CI = confidence interval; Li = lithium; TCAs = tricyclic antidepressants; AAPs = atypical antipsychotics; AEDs = antiepileptic drugs; T3 = tri-iodothyronine; CBT = cognitive behaviour therapy; BUS = buspirone. Li = lithium; TCAs = tricyclic antidepressants; AAPs = atypical antipsychotics; BUS = buspirone; AEDs = antiepileptic drugs; T3 = tri-iodothyronine; CBT = cognitive behaviour therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies were conducted on SSRI nonresponders. Most of those studies were open label, and the results confirmed that augmentation with lithium was effective in TRD (Table 2) [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Level 1: Lithiummentioning
confidence: 96%